The housework in qualitative research - Barboza-Palomino, Miguel (2015)
Book-review of: Minayo, M. C. S., Ferreira, S. & Gomes, R. (2012). Investigación Social. Teoría, método y creatividad. Buenos Aires: Lugar Editorial